PENERAPAN STRATEGI READING ALOUD DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII C PADA MATA PELAJARAN AL-QUR’AN HADIS DI MTs THAMRIN YAHYA RAMBAH HILIR KABUPATEN ROKAN HULU, RIAU - BASHORI BASHORI (IKIP PGRI MADIUN, 2017)
AbstractThis research is motivated by the low result of learning the Quran Hadith eighth grade students understand the content of C in the material content of the surah al-Humazah and at-Takatsur MTs Yahya Thamrin Rambah Rokan Hilir Hulu. Of the 28 students of class VIII C who received grades above KKM amounted to 75 only 10 people, while 18 other students received grades below KKM. Based on these findings, the authors sought to improve student learning outcomes VIII class C through a classroom action research strategy Reading Aloud. Subjects in this study were teachers and all the students of class VIII C totaling 28 students consisting of 8 male students and 20 female students. While the object of this study is the implementation strategy of Reading Aloud to improve learning outcomes Qur’an Hadith eighth grade students understand the content of C in the material content of the surah al-Humazah and at-Takatsur MTs Yahya Thamrin Rambah Rokan Hilir Hulu. Collecting data in this study using observation, achievement test, interview, and documentation. After processing the data, and then analyzed using descriptive analysis techniques of qualitative and quantitative. Meanwhile, to test the hypothesis of this study were analyzed by the test “t”. From the results of data analysis can be concluded that the implementation strategy of Reading Aloud to improve learning outcomes Qur’an Hadith eighth grade students understand the content of C in the material content of the surah al-Humazah and at-Takatsur, from an average of 69.86 in the prior action became the first cycle of 76.29 and 81.79 in the second cycle. Hypothesis test results obtained price amounted to 19.494 much greater than the value table at a significance level of 5% and 1%. Thus the alternative hypothesis (Ha) is acceptable. Based on the conclusions of this study, the authors advise that teachers would Quran Hadith should be able to apply a variety of active learning strategies, especially strategies Reading Aloud on an ongoing basis to overcome the low results for students at the school. AbstrakPenelitian ini dilatarbelakangi oleh rendahnya hasil belajar Al-Qur’an Hadits siswa kelas VIII C pada materi memahami isi kandungan surat al-Humazah dan at-Takatsur di MTs Thamrin Yahya Rambah Hilir Kabupaten Rokan Hulu. Dari 28 orang siswa kelas VIII C yang memperoleh nilai di atas KKM sebesar 75 hanya 10 orang, sedangkan 18 orang siswa lainnya memperoleh nilai di bawah KKM. Berdasarkan hasil temuan inilah, maka penulis berusaha untuk meningkatkan hasil belajar siswa kelas VIII C melalui sebuah penelitian tindakan kelas dengan menerapkan strategi Reading Aloud. Subjek dalam penelitian ini adalah guru dan seluruh siswa kelas VIII C yang berjumlah 28 orang siswa yang terdiri dari 8 orang siswa laki-laki dan 20 orang siswa perempuan. Sementara objek penelitian ini adalah penerapan strategi Reading Aloud untuk meningkatkan hasil belajar Al-Qur’an Hadis siswa kelas VIII C pada materi memahami isi kandungan surat al-Humazah dan at-Takatsur di MTs Thamrin Yahya Rambah Hilir Kabupaten Rokan Hulu. Pengumpulan data dalam penelitian ini menggunakan teknik observasi, tes hasil belajar, wawancara, dan dokumentasi. Setelah dilakukan pengolahan data, selanjutnya dilakukan analisis dengan menggunakan teknik analisis deskriptif kualitatif dan kuantitatif. Sedangkan untuk menguji hipotesis penelitian ini, dianalisis dengan uji tes “t”. Dari hasil analisis data dapat disimpulkan bahwa penerapan strategi Reading Aloud dapat meningkatkan hasil belajar Al-Qur’an Hadis siswa kelas VIII C pada materi memahami isi kandungan surat al-Humazah dan at-Takatsur, dari rata-rata sebesar 69,86 pada sebelum tindakan menjadi 76,29 pada siklus I dan 81,79 pada siklus II. Hasil uji hipotesis diperoleh harga t sebesar 19,494 jauh lebih besar dari nilai t pada taraf signifikan 5% maupun 1%. Dengan demikian hipotesis alternatif (Ha) dapat diterima. Berdasarkan hasil kesimpulan penelitian ini, maka penulis memberikan saran agar kiranya guru Al-Qur’an Hadits hendaknya dapat menerapkan berbagai strategi pembelajaran aktif, khususnya strategi Reading Aloud secara berkesinambungan guna mengatasi rendahnya hasil belajar siswa di sekolah.